Learning from implementation of a COVID case management desk guide and training: a pilot study in Sierra Leone - Sophie Witter; Guanyang Zou; Kiran Cheedella; John Walley; Haja Wurie (BMC, 2023)
Abstract Background When the COVID pandemic hit the world, there was need for applied guides and training materials to support frontline health care staff to manage patients effectively and safely and to educate themselves and communities. This article reports on the development and piloting of such a set of materials in Sierra Leone, which were based on international evidence but adapted to the local context. Reflecting on this experience, including community and health system barriers and enablers, is important to prepare for future regional shocks. Methods This study, in Bombali district in 2020, piloted user-friendly COVID guides for frontline health workers (the intervention), which was evaluated using facility checklists (pre and post training), routine data analysis and 32 key informant interviews. Results Key informants at district, hospital and community health centre levels identified gains from the training and desk guides, including improved diagnosis, triaging, infection prevention and management of patients. They also reported greater confidence to share messages on protection with colleagues and community members, which was needed to encourage continued use of essential services during the pandemic. However, important barriers were also revealed, including the lack of testing facilities, which reduced the sense of urgency, as few cases were identified. Actions based on the Ebola experience, such as setting up testing and isolation centres, which the community avoided, were not appropriate to COVID. Stigma and fear were important factors, although these were reduced with outreach activities. Supplies of essential medicines and personal protective equipment were also lacking. Conclusion This pilot study demonstrated the relevance and importance of guides adapted to the context, which were able to improve the confidence of health staff to manage their own and the community's fears in the face of a new pandemic and improve their skills. Previous epidemics, particularly Ebola, complicated this by both creating structures that could be revitalised but also assumptions and behaviours that were not adapted to the new disease. Our study documents positive adaptations and resilience by health staff but also chronic system weaknesses (particularly for medicines, supplies and equipment) which must be urgently addressed before the next shock arrives.